Retrofitting of Damage Rail Bridge Girder and Its Performance Evaluation - Shukla A.K.; Maiti P.R.; Rai G. (My University, 2025)
Strengthening of prestressed girder using FRP has rarely been performed because prestressed girder has excellent strength under service load in both tension and compression. In this study, retrofitting of a 59-year-old prestressed bridge of Indian railway at Ratlam has been executed in which multiple vertical cracks visualized in tension zone and surface deterioration were observed. Due to this, deterioration speed of the trains over the bridge was restricted up to 20 km/h. The PSC girders of the bridge were strengthened by using prestressed carbon fiber. Serviceability of the structure was monitored before strengthening and after strengthening of the bridge girder. Deflections and natural frequencies after strengthening of girder were monitored for 481 days to ascertain the improvement and consistency in behavior of girder. After strengthening, the considerable decrement in deflection was noted by dint of the speed limit of the train which is recommended to increase up to 100 km/h. © 2020, ASM International.